Opioid-Free Anesthesia as a Part of Multimodal Anesthesia Approach in Modified Radical Mastectomy: A Case Report - Togi Stanislaus Patrick; Sinardja, Cynthia Dewi; Senapathi, Tjokorda Gde Agung; Ra Ratumasa, Marilaeta Cindryani (Majalah Anestesia & Critical Care, 2025)
Introduction: The shift towards opioid-free anesthesia (OFA) reflects a growing effort to enhance patient safety and reduce opioid-related adverse effects, particularly in oncology surgeries such as modified radical mastectomy (MRM). Case Description: We describe the anesthetic management of a 51-year-old female with infiltrating ductal carcinoma of the left breast who underwent MRM under an opioid-free anesthetic protocol. Induction was performed with propofol via target-controlled infusion (TCI), followed by intraoperative dexmedetomidine infusion for sedation and analgesia. An ultrasound-guided erector spinae plane (ESP) block at the T5 level was performed with 0.375% ropivacaine and dexamethasone to provide regional analgesia. Intraoperative hemodynamics remained stable, no rescue opioids were required, and blood loss was minimal. Postoperative pain control was achieved with a low-dose dexmedetomidine infusion, intravenous ketorolac, and oral paracetamol. The patient reported minimal pain (NRS 0–1/10), had no nausea, vomiting, or respiratory depression, and recovered uneventfully. Conclusion: OFA offers oncological advantages by preserving immune function and reducing tumor- promoting factors, making it a promising alternative in cancer surgery. This report supports the feasibility and benefits of OFA in major breast cancer procedures, underscoring its role in enhancing recovery and potentially improving long-term oncologic outcomes.